(untitled) (ModaPalavra e-periódico, 2026)
This article investigates how the Generative Artificial Intelligence (GAI) model ChatGPT-4 interprets and reproduces visual discourses of femininity based on popular trends from the TikTok platform. The study aims to analyze the meaning effects present in images produced by the DALL-E model, derived from the hashtags #cleangirl and #patynordestina, observing how global and local aesthetic patterns are represented and re-signified. The research adopts a qualitative approach, grounded in bibliographic review and discursive semiotic analysis, to examine the planes of expression and content within the generated images. The results indicate that GAI tends to reproduce hegemonic patterns of beauty and behavior, reinforcing Eurocentric and idealized stereotypes. While the #cleangirl trend emphasizes the valorization of cleanliness and aesthetic neutrality, #patynordestina demonstrates the fetishization of cultural otherness, transforming regional references into stylized and superficial elements. It is concluded that GAI still lacks cultural sensitivity and diversity within its datasets, perpetuating biases and imagetic standardizations that constrain the plurality of female representations in the digital sphere.